Pengaruh Kecerdasan Numerik dan Motivasi Belajar terhadap Kemampuan Pemecahan Masalah Matematika - Rodiah Rodiah; Supardi Supardi (International Forum of Researchers and Lecturers, 2025)
The study aims to determine: 1) The influence of numerical intelligence and learning motivation together on the mathematical problem solving ability of class XII TKJ students of SMK Negeri 1 Sukaluyu Cianjur. 2) The influence of numerical intelligence on the mathematical problem solving ability of class XII TKJ students of SMK Negeri 1 Sukaluyu Cianjur. 3) The influence of learning motivation on the mathematical problem solving ability of class XII TKJ students of SMK Negeri 1 Sukaluyu Cianjur. The study was conducted using a survey method. The population was class XII TKJ students of SMK Negeri 1 Sukaluyu Cianjur with a sample size of 85 students. The sampling technique used was random sampling. The research instruments used were essay-based mathematical problem solving ability tests, multiple-choice numerical intelligence instruments, and Likert-scale learning motivation instruments. Data analysis using multiple linear regression analysis. The results of the hypothesis testing obtained the following conclusions: 1) There is a significant influence of numerical intelligence and learning motivation together on mathematical problem solving ability, this is evidenced by Sig. 0.000 < 0.05 and Fcount > Ftable, which is 3.57 > 3.12. 2) There is a significant influence of numerical intelligence on mathematical problem solving ability, this is proven by Sig. 0.000 < 0.05 and tcount > ttable, which is 5.7 > 2.00. 3) There is a significant influence of learning motivation on mathematical problem solving ability, this is proven by Sig. 0.000 < 0.05 and tcount > ttable, which is 5.7 > 2.00. The results of this study are useful for improving the quality of learning and improving mathematical problem solving ability at the vocational high school level.